PENGARUH TERAPI MUSIK GAMELAN JAWA TERHADAP TINGKAT PENURUNAN INSOMNIA PADA LANSIA - Umah, Khoiroh; Twistiandayani, retno (Jurnal Penelitian Multidisiplin, 2023)
Music therapy is an attempt to improve physical and mental quality with sound stimuli that are beneficial to physical and mental health. Music therapy is done by playing Javanese gamelan music to lower insomnia levels in the elderly. The purpose of this study was to explain the influence of Javanese gamelan music therapy to the level of insomnia decreased in the elderly.This research uses Pre Experimental method in one group (One Group Pre test-Post test Design) Sampling method using purposive sampling The amount of population in this study as 30 respondents while the sample taken as many as 16 respondents who intervened using Javanese gamelan music therapy. Javanese gamelan music performed 3x / week for 2 weeks at night before sleep Independent variables of Javanese gamelan music therapy Dependent variable is insomnia The data were collected using KSPBJ-IRS questionnaire Data analysis using Wilcoxon Signed Rank Test with a default value <0.05.The results showed that before intervention the average value of insomnia decreased 3.12 and after intervention the average value of insomnia decrease level 2.31 significant value (2-tailed) = 0.00 which means that (a count) <0,05 then H1 accepted and H0 rejected means there is influence of Javanese gamelan music therapy to the level of insomnia decreased in the elderly.